2018
DOI: 10.1021/acs.macromol.8b00907
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide-Mediated Alkyl–Alkyl Coupling of Dialkylzinc: A Useful Tool for Synthesis of ABA-Type Olefin Triblock Copolymers

Abstract: A practical and simple method for the preparation of ABA-type olefin triblock copolymers, e.g., PE-b-poly­(ethylene-co-propylene)-b-PE, has been described. The performance of the so-called “coordinative chain transfer polymerization” (CCTP) by sequential feed of ethylene and ethylene/propylene mixed gas generated a Zn-bound diblock copolymer (i.e., (PE-b-poly­(ethylene-co-propylene)­yl)2Zn). Treatment of the Zn-bound diblock copolymer with lauroyl peroxide (CH3(CH2)10C­(O)­O-OC­(O)­(CH2)10CH3) led to a C­(sp3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…The gel permeation chromatography (GPC) data were obtained in 1,2,4-trichlorobenzene at 160 • C using a PL-GPC 220 system equipped with an RI detector and two columns [PLgel mixed-B 7.5 × 300 mm from Varian (Polymer Lab)]. (1-Octyl) 2 Zn and (1-hexyl) 2 Zn were prepared and purified as described in the literature [26]. n-BuLi and sec-BuLi were used as neat oils, while t-BuLi as solid after removing the solvent inside the glove box.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The gel permeation chromatography (GPC) data were obtained in 1,2,4-trichlorobenzene at 160 • C using a PL-GPC 220 system equipped with an RI detector and two columns [PLgel mixed-B 7.5 × 300 mm from Varian (Polymer Lab)]. (1-Octyl) 2 Zn and (1-hexyl) 2 Zn were prepared and purified as described in the literature [26]. n-BuLi and sec-BuLi were used as neat oils, while t-BuLi as solid after removing the solvent inside the glove box.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, 1 is capable of incorporating a significant amount of α-olefins in an ethylene/α-olefin copolymerization [47]. A minimal amount of MMAO (50 µmol-Al) had to be fed, in addition to the CTA (1-hexyl)2Zn (100 or 200 µmol-Al), to realize the full activity of 1, even though PO chain growth from some Al-sites was unavoidable [26,48,49]. The generated (polyolefinyl)2Zn was treated with t- In contrast, we found that (tBu) 2 Zn was decomposed at 130 • C, and a black solid precipitated when a solution of (tBu) 2 Zn in decane was heated at 130 • C. Isobutene and H 2 signals were detected in the 1 H NMR spectrum when the reaction was performed in a sealed tube in toluene-d 8 (Scheme 2b).…”
Section: Attempts To Synthesize Block Copolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…In CCTP performed with I, PO chains are generated as a form of (polyolefinyl) 2 Zn with a rather narrow molecular-weight distribution (M w /M n ≈ 1.7) and with negligible formation of PO chains not attached to Zn sites, owing to a feature of I ensuring the rapid alkyl exchange process and the absence of the β-elimination process [16,18]. Due to these characteristics, it is possible to grow PO chains with variation of ethylene/α-olefin composition, either by sequential variation of the ethylene/α-olefin feed ratio or by means of a dual catalytic system with distinctly different monomer reactivity, enabling commercial production of olefin block copolymers composed of hard crystalline and soft rubbery PO blocks [19][20][21][22][23]. A method has also been developed to grow polystyrene (PS) chains further from the CCTP product (polyolefinyl) 2 Zn, thereby allowing for the synthesis of commercially relevant PO-block-PS and PS-block-PO-block-PS via one-pot synthesis [14,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%